ANALISIS METODE SIMA’I DENGAN MEDIA AUDIO MUROTTAL TERHADAP KEMAMPUAN MENGHAFAL ANAK USIA DINI DI TAUD SAQU PONPES KARANGASEM PACIRAN LAMONGAN - Rosyida, Farah Fauzia; Ratno Abidin; Tri Kurniawati; Naili Sa'ida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Memorizing verses in Qur'an is good for early childhood development if viewed cognitively. To achieve this, it is inseparable from the influence of the right methods and media. This research aims to analyze the application of the sima’i method with murottal audio media on the ability to memorize the Qur'an in early childhood at Boarding School of TAUD SAQU in Karangasem Paciran Lamongan, as well as identifying the faktors that affected the memorization method. This research used a qualitative approach with observation, interview, and documentation techniques. The results showed that the application of the sima’i method with murottal audio media on a regular and structured basis was effective in improving children's memorization skills, with the average memorization increasing from 5 verses to 10 verses per week. The faktors that affected the success of this method included children's motivation and concentration, parental support, and a conducive learning environment. This research concluded that the sima’i method with murottal audio media can be used as an effective alternative in learning to memorize the Qur'an in early childhood, with the support of parents and a conducive environment as important faktors supporting its success. This study recommends wider adoption of the sima’i method as well as further research used other media to improve the effectiveness of learning.